Can the ketogenic diet improve the hamstring muscle rupture? A narrative review - Saeid Emamdoost (Journal of Sports and Rehabilitation Sciences, 2024)
The ketogenic diet has garnered significant attention for its potential benefits in various health areas, including weight loss, neurological conditions, and metabolic diseases. Characterized by high fat, moderate protein, and low carbohydrate intake, the ketogenic diet induces a state of ketosis, where the body shifts its primary energy source from glucose to ketones derived from fat. This metabolic shift leads to numerous physiological changes, some of which may benefit muscle health and recovery. Hamstring muscle ruptures, common among athletes and physically active individuals, require a combination of rest, physical therapy, and nutritional interventions to reduce inflammation, promote muscle repair, and enhance overall recovery outcomes. Given the known anti-inflammatory and muscle-sparing effects of the ketogenic diet, there is growing interest in exploring its potential role in the recovery of hamstring muscle ruptures. The primary objective of this research is to investigate and potentially validate the ketogenic diet's potential benefits in improving hamstring muscle rupture recovery. This article will explore the underlying mechanisms through which the ketogenic diet may influence muscle healing, review existing studies and clinical evidence, and discuss the potential benefits and challenges of integrating the ketogenic diet into rehabilitation protocols for muscle injuries.